Stratificational Analysis of a Hortatory Text: I Corinthians 8.1-11.1 - Youngman, Scott (Arlington, TX, USA University of Texas at Arlington, 1987)
Publication status: Published
Keywords: STRATIFICATIONAL GRAMMAR